Marketing partnerski w instytucjach bankowych - Jakubowska, Agata (Partnership Marketing in Banks, 2006)
In the paper author was been presenting adaptation relationship marketing in the banks. Relationship marketing is an instrument using to build permanent, partner relations with client. Winning the loyal client is possible when the banks use relationship marketing. Bank's market success is based on client and his satisfaction. Banks take advantage by personal and private banking for creation permanent, partner relations with client.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 436-442